2019
DOI: 10.1111/1462-2920.14523
|View full text |Cite
|
Sign up to set email alerts
|

The pleiotropic Legionella transcription factor LvbR links the Lqs and c‐di‐GMP regulatory networks to control biofilm architecture and virulence

Abstract: Summary The causative agent of Legionnaires' disease, Legionella pneumophila, colonizes amoebae and biofilms in the environment. The opportunistic pathogen employs the Lqs (Legionella quorum sensing) system and the signalling molecule LAI‐1 (Legionella autoinducer‐1) to regulate virulence, motility, natural competence and expression of a 133 kb genomic “fitness island”, including a putative novel regulator. Here, we show that the regulator termed LvbR is an LqsS‐regulated transcription factor that binds to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 85 publications
2
50
0
Order By: Relevance
“…The lack of phenotype for Δ lqsR prompted us to look for an alternative response regulator possibly controlling phenotypic heterogeneity. The transcription factor LvbR is negatively regulated by the sensor kinase LqsS 63 . Deletion of lvbR led to a loss in nongrowers in A. castellanii at 24 h p.i.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of phenotype for Δ lqsR prompted us to look for an alternative response regulator possibly controlling phenotypic heterogeneity. The transcription factor LvbR is negatively regulated by the sensor kinase LqsS 63 . Deletion of lvbR led to a loss in nongrowers in A. castellanii at 24 h p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the size of the nongrowing intracellular L. pneumophila subpopulation seems also to be controlled by the recently characterized DNA-binding transcription factor LvbR 63 , rather than the response regulator LqsR 33 . LvbR links the Lqs and c-di-GMP regulatory networks 63 , and the comparative proteomics approach documented in this study revealed that the intracellular nongrowing subpopulation shows a 10-30-fold enrichment in various diguanylate cyclases presumably producing c-di-GMP. Further studies will address the role of the second messenger c-di-GMP in regulating intracellular virulent L. pneumophila persisters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reciprocal interaction between QS and c-di-GMP regulatory circuits are well documented, with a general trend of dominant negative control of QS by c-di-GMP (Hochstrasser et al 2019;Lin Chua et al 2017;Waldron et al 2019;Yang et al 2017). In S. meliloti, elevated levels of c-di-GMP repressed transcription of AHL synthase enzyme sinI and lowered abundance of QS signal AHL molecules in the culture medium (Schäper et al 2016) (Figure 3).…”
Section: Regulatory Connections To Qsmentioning
confidence: 95%
“…Intriguingly, the c‐di‐GMP and quorum sensing regulatory networks are linked in L. pneumophila . The sensor kinase LqsS negatively regulates a pleiotropic transcription factor termed LvbR ( Legionella virulence and biofilm regulator), which in turn negatively regulates an inhibitor of the diguanylate cyclase Lpg1057 (Hochstrasser et al, ; Tiaden et al, ). LvbR controls pathogen–host cell interactions, biofilm architecture and natural competence.…”
Section: Introductionmentioning
confidence: 99%